Coexpression of soluble and membrane-bound avian influenza virus H5 by recombinant Newcastle disease virus leads to an increase in antigen levels. (25th May 2020) - Murr, Magdalena; Karger, Axel; Steglich, Constanze; Mettenleiter, Thomas C.; Römer-Oberdörfer, Angela
Abstract : Newcastle disease virus (NDV) vectors expressing avian influenza virus (AIV) haemagglutinin (HA) of subtype H5 simultaneously protect chickens from Newcastle disease (ND) as well as avian influenza (AI). The expressed, membrane-bound surface protein HA is incorporated into virions while soluble HA has been described as a potent antigen. We tested whether co-expression of both HA variants from the same NDV vector increased the overall level of HA, which could be important for optimal immunogenicity. Recombinant NDVsolH5_H5 co-expressed membrane-bound H5 of highly pathogenic (HP) AIV H5N1, detectable in infected cells, and soluble H5, which was secreted into the supernatant. This virus was compared to recombinant NDV that express either membrane-bound (rNDVH5) or soluble H5 (rNDVsolH5). Replication in embryonated chicken eggs (ECEs) and in cell culture, as well as pathogenicity in ECEs, was not influenced by the second heterologous transcriptional unit. However, the co-expression of soluble H5 with membrane-bound H5 increased total protein level about 5.25-fold as detected by MS quantification. Hence, this virus is very interesting as a vaccine virus in chickens against HPAIV infections in situations in which previous H5-expressing NDVs have reached their limit, such as in the face of pre-existing AIV maternal immunity.